Community Education and Neoliberalism - Fitzsimons, Camilla (Springer Nature, 2025)
This open access book, now in its second edition, offers a powerful analysis of adult and community education at a time of rising inequality and diminishing state support. Grounded in both Irish and international contexts, this edition again challenges the impact of neoliberal agendas on grassroots community education and makes a convincing case for reclaiming community education’s radical, consciousness-raising agenda. The book is theoretically rooted in critical feminist pedagogy and draws on real-world examples to present key aspects of this approach to adult learning in a clear, accessible, and practical way. Community Education and Neoliberalism exposes the extent to which market-driven forces and managerialist agendas are eroding the transformative nature of adult and community education. The author examines the impact of neoliberal government lifelong learning policies, the potential drawbacks of professionalising community education and the perils of accreditation systems when marketisation becomes the principal focus. But this book does not simply offer a critique — it also presents practical pathways to revitalise community education, ensuring it continues to be a part of the struggle for a better world which, the author argues, can only be achieved through collective action. The book is essential reading and a call to action for students, educators, activists and policymakers alike, or indeed or anyone who is passionate about equality and social justice.